Comparative Analysis of Laparoscopic and Open Tubal Ligation: Insights from a Retrospective Study in a Tertiary University Hospital - Naser Al-Husban; Somaya Al Kiswani; Nadeen Al-Falooji; Abdulla Alzibdeh; Zaid Fakhouri; Murad Haddad; Mai Al-Adwan; Alhsna′ Alhusban; Leen Al-Omari; Reem Abuhamdah (Clinical and Experimental Obstetrics & Gynecology)
Background: Female sterilization remains a prevalent contraceptive method globally, despite a declining trend in prevalence over the past decades. Methods: To compare the outcomes of tubal ligation between laparoscopic and open surgical approaches, conducted at the Jordan University Hospital from 2010 to 2021. Results: 242 females underwent tubal ligation with 131 had open surgery and 111 had laparoscopic surgery. The median follow-up period for the cohort was 8 years. For the entire study cohort, the mean age at the time of surgery was 37.77 years (standard deviation (SD) = 4.589). A statistically significant (p < 0.0001) difference in age was found, with mean age being older in the laparoscopy group. However, there were no significant differences between the two groups in terms of gravidity (p = 0.9499) or parity (p = 0.4867). Remarkably, only two pregnancies were documented during the follow-up period, both of which were observed in the laparoscopic surgery group. Overall free-from-pregnancy rate at 8 years was 98.79%; 97.59% in the laparoscopy group and 100% in the open surgery group. Conclusions: Both open and laparoscopic tubal sterilization are equally effective permanent contraceptives. While our study contributes to the understanding of tubal ligation outcomes, further research, particularly in developing countries like Jordan, is warranted to address the unique needs and challenges of diverse populations in reproductive healthcare.